Microsatellite- based phylogeny of Indian sheep breeds - RAMACHANDRAN, A; THIRUVENKADAN, A K; KATHIRAVAN, P; SARAVANAN, R; PANNEERSELVAM, C; ELANGO, A (The Indian Journal of Animal Sciences, 2015)
Genetic diversity of south Indian meat type breeds was investigated by means of 15 ovine microsatellite markers. All used microsatellites amplified well and exhibited polymorphisms. A wide range of genetic variability was observed as allele varied from 4 to 10 in Madras Red; 4 to 10 in Mecheri; 4 to 12 in Pattanam; and 3 to 12 in Nellore sheep breeds. The mean number of alleles observed in Madras Red, Mecheri, Pattanam and Nellore breeds were 6.5, 6.7, 7.0 and 7.2 respectively. Average observed and expected heterozygosities over the different breeds were 0.23 to 0.87 and 0.347 to 0.827 respectively. The most diverse sheep breed was Nellore breed and the least diverse breed was Madras Red, which had the lowest total number of alleles (na=98) and lowest average observed (Ho=0.576) and expected (Ho=0.594) heterozygosities. The multi-locus mean between-population variability (FST) values indicated that about 5.60% of the total genetic variation was explained by population differences, whereas, the remaining 94.40% is due to differences among individuals within breeds. The values of FIT in the sub population for the most of markers were positive which showed the deficiency of heterozygotes. The DA genetic distance and FST distances between pairs of breeds revealed that the lowest distance was between Madras Red and Mecheri and the highest between Mecheri and Nellore breeds. Analysis of individual genotypes provided valuable information for understanding intra and inter-population genetic differences and helps in planning genetic improvement and conservation strategies for further improvement and sustainable utilization.